2018
DOI: 10.1159/000487464
|View full text |Cite
|
Sign up to set email alerts
|

Altered Long Noncoding RNA and Messenger RNA Expression in Experimental Intracerebral Hemorrhage - a Preliminary Study

Abstract: Background/Aims: Functional recovery in the chronic phase is a difficult problem in intracerebral hemorrhage (ICH) treatment. Long noncoding RNAs (lncRNAs) are demonstrated to be involved in central nervous system (CNS) disorders. However, the roles of lncRNAs in post-ICH injury and repair are poorly understood, especially those that may be attributed to long-term neurological deficit. The present study depicted the lncRNA and messenger RNA (mRNA) profile by microarray at late stage after an experimental ICH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Then, the arrays were scanned using the Agilent Microarray Scanner and were finally analyzed using the Agilent Feature Extraction software. Differentially expressed transcripts were identified by fold-change screening at a threshold of ≥2-fold and a p-value of <0.05 5 . Pathway analysis was used to study the significant signaling pathways of the differentially expressed genes.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the arrays were scanned using the Agilent Microarray Scanner and were finally analyzed using the Agilent Feature Extraction software. Differentially expressed transcripts were identified by fold-change screening at a threshold of ≥2-fold and a p-value of <0.05 5 . Pathway analysis was used to study the significant signaling pathways of the differentially expressed genes.…”
Section: Methodsmentioning
confidence: 99%
“…It has recently been shown that BYHWD could exposure augmented angiogenetic miRNAs in ischemic stroke 24. Additionally, we first found that lncRNAs were possible therapeutic targets of BYHWD in ICH treatment 25, 26. Nevertheless, considering a huge amount of ncRNAs, more functional ncRNAs are needed to reveal the therapeutic mechanisms of BYHWD in ICH.…”
Section: Introductionmentioning
confidence: 94%
“…zone. 7 Thus, hypoxia cannot account for the post-ICH miR-24 change. After ICH, abundant thrombin is released from the hematoma, infiltrating into the cerebral parenchyma.…”
Section: Thrombin Elevated Mir-24 Expression and Angiogenesis After Ichmentioning
confidence: 99%
“…However, unlike in ischemic stroke, the perihemorrhagic region is a normoxic microenvironment. 7 Although HIF-1α expression is generally considered to be increased by hypoxia, there is still accumulating evidence showing that under normoxic conditions, many growth factors, cytokines, and other signaling molecules can activate HIF-1α. 8,9 Thrombin is a critical signaling molecule cleaved from the proenzyme prothrombin after bleeding.…”
mentioning
confidence: 99%